Justice In Efforts To Improve Employment Welfare - Rachmad Abduh (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Paradigm of development in the field of human activity should be revised, which previously thought of seeing workers as a source of production or part of goods, should be changed into workers who are full Indonesians or as subjects/tools of the development process. with their dignity. This paradigm shift has the effect of guiding and determining the legal politics of public policy in the field of human activity through changes in composite solutions by seeing workers as subjects and minds that require all aspects of the whole. The crime is often seen by the employee who receives it from the employer, so the employer does not get the benefit. There is a difference between employees and non-employees. The current law is not able to improve the standard of living according to the wishes of the workers. This is because many judges are professionals. The current law is not able to improve the standard of living according to the wishes of the workers. This is because many judges are professionals